2010
DOI: 10.1038/onc.2009.516
|View full text |Cite
|
Sign up to set email alerts
|

Knock in of the AKT1 E17K mutation in human breast epithelial cells does not recapitulate oncogenic PIK3CA mutations

Abstract: An oncogenic mutation (G49A:E17K) in the AKT1 gene has been described recently in human breast, colon, and ovarian cancers. The low frequency of this mutation and perhaps other selective pressures have prevented the isolation of human cancer cell lines that harbor this mutation thereby limiting functional analysis. Here, we create a physiologic in vitro model to study the effects of this mutation by using somatic cell gene targeting using the nontumorigenic human breast epithelial cell line, MCF10A. Surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
68
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 30 publications
8
68
2
Order By: Relevance
“…Past studies comparing overexpression of a mutant cDNA to single nucleotide knockin of mutant oncogenes have shown dramatic differences in signaling and transformed phenotypes (11)(12)(13). Additionally, we have shown KRAS G12V mutations, as single copies, have relatively little effect in breast epithelial cells, but have a profound effect on cancerous phenotypes and tumorigenicity when coupled with a PIK3CA oncogenic hotspot mutation (14).…”
mentioning
confidence: 65%
“…Past studies comparing overexpression of a mutant cDNA to single nucleotide knockin of mutant oncogenes have shown dramatic differences in signaling and transformed phenotypes (11)(12)(13). Additionally, we have shown KRAS G12V mutations, as single copies, have relatively little effect in breast epithelial cells, but have a profound effect on cancerous phenotypes and tumorigenicity when coupled with a PIK3CA oncogenic hotspot mutation (14).…”
mentioning
confidence: 65%
“…It is possible that AKT1 or β-catenin mutation alone is able to produce a benign tumor but not a malignant tumor. AKT1 mutation itself has a weak transforming activity (35), which might make the cells proliferate and change morphology but not acquire the capability to further progress to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of pharmacologic inhibition of the protein in models of breast and urothelial carcinoma with endogenous AKT1 E17K mutation have not been reported. Lauring and colleagues reported that AKT1 E17K had minimal phenotypic consequences and failed to induce ongogenic transformation of MCF10 breast epithelial cells, whereas PIK3CA E545K and PIK3CA H1047R mutations were transforming in the same cells, leading them to suggest that these mutations may not be functionally equivalent, and that cooperating genetic changes are required for AKT1 E17K to transform these cells (17). In breast cancer, PIK3CA and AKT1 mutations tend to be mutually exclusive, which suggests that either these mutations do have some redundancy of function, or that PIK3CA is not cooperative with AKT1 for oncogenic transformation of breast epithelial cells, or indeed progression of breast tumors to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The E17K mutation has been shown to constitutively activate AKT1 by increased localization to the plasma membrane, where it stimulates downstream signaling and can transform Rat1 fibroblasts and induce leukemia in mice (15). Although knock-in of AKT1 E17K into isogenic MCF-7 breast cancer cells depleted of endogenous PIK3CA E545K restored proliferation in vitro and tumor growth in vivo (16), knock-in of E17K into the AKT1 gene of nontransformed MCF10A mammary epithelial cells had minimal phenotypic consequences and did not recapitulate the transforming properties induced by somatic cell knock in of PIK3CA hotspot mutations (17). In addition, the consequences of directly inhibiting this target in endogenous models of breast and urinary bladder cancer have not been reported.…”
Section: Introductionmentioning
confidence: 99%